PENGARUH PEMBAGIAN LABA PERUSAHAAN, PROFITABILITAS DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PERUSAHAAN - La Sudarman; Poniasih Lelawatty; Wilda Fatmala (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to determine the effect of dividend per share, profitability, and capital structure on share prices, partially and simultaneously, for automotive companies indexed by the Indonesian Sharia Stock Index. Data processing in this research uses quantitative data analysis and uses Views version 9. The samples in this research are automotive subsector companies indexed by the Indonesian Sharia Stock Index (ISSI), totaling 10 companies over the 4-year period 2018–2021. The research results found that partial dividends per share had no effect on share prices, profitability, and capital structure had a significant effect on share prices. Simultaneously, dividend per share, profitability, and capital structure have no effect on share prices.